STUDENT RESPONSE TO DIGITAL MODULE OF WORK AND SIMPLE MACHINES FOR CLASS VIII JUNIOR HIGH SCHOOL - Alfensianita, Claudia; Mering, Aloysius; Enawaty, Eny (Universitas Tanjungpura, 2022)
This research aims to know the student response to digital module of work and simple machine materials for science learning in Junior High School. The module is equipped with images, videos, animations, and audio. The discussion section on sample questions in the module integrates 5 problem-solving indicators from the Robust Assessment Instrument For Student Problem Solving developed by Docktor and Heller, namely useful description, physics approach, specific application of physics, mathematical procedures, and logical progression. The digital module is designed based on the Dick and Carey learning system design. The data obtained from student response questionnaire given to 30 eighth graders after the study using digital module. The student response questionnaire consists of 15 statements. Student responses classified into three aspects, interest, material, and languange. The results showed that student responses in the interest aspect get score percentage 90%, material aspect get score percentage 88%, and languange aspect get score percentage 94%. The percentage score average for three aspects is 90.6% with very good classification.